Implementasi Kepemimpinan Kepala Sekolah Dalam Perencanaan Pembiayaan Pendidikan - Shelty Deity Meity Sumual; Meytha Meyske Wongkar; Samuel Harry Mossey; Davison Pagawak (Departement of Mathematics Education, 2024)
This study aims to determine the implementation of the principal's leadership in education financial management. Financing management is critical to the success of the education sector. As a sector, funding is essential for the development and maintenance of quality education programs and initiatives, so it requires a strong foundation and leaders to bring educational institutions to be better. The principal as a leader is responsible for the achievement of the expected educational goals. This research uses the research method of literature study. This approach is a research method by collecting and analyzing existing literature on a particular topic or field of study. The result of this study is that school principals play an important role in managing education finances and implementing effective leadership strategies can significantly improve resource management and utilization. One key aspect of effective leadership is the ability to communicate financial information clearly and transparently to all stakeholders involved, including teachers, parents, and the wider community. This can be achieved through regular financial reports and meetings that provide an overview of the school's financial situation and how funds are allocated